Hubungan Interaksi Sosial dengan Tingkat Depresi pada Lansia di Panti Werdha Pangesti Lawang - Aulia Puspitasari; Lilla Maria (Jurnal Ilmiah Kesehatan Rustida, 2020)
Elderly is someone who has aged 60 years. Biologically, the elderly have characteristics that can be seen in the real changes in the physical and mental state. One very important factor for preventing depression in old age in to support family. Family support in the form of a joint attitude and acceptance that can help the age old problem of family support has an important role in the treatment process, because the family could provide the impetus both in terms of physical or psychological significance sufferers of depression. Objective to know the relationship of social interaction with the level of depression in elderly in Nursing Pangesti Lawang. Design research using the analytic correlational with cross sectional approach. Samples in research 40 elderly. This research uses a sampling technique total sampling. The method of data correction using the guidelines of the interview. Data analysis using the Spearman correction test. The results of this study indicate that the level of depression in the elderly of 40 respondents found most depressed levels under normal circumstances with good social interaction 29 respondents (72.5%) and a small percentage of mild depression with moderate social interaction 11 respondents (27.5%).Spearman correlation test results obtained (r count) of -713 with a p-value of 0,000 so that it can be concluded that there is a relationship between social interaction with the level of depression in elderly in Nursing Werdha Pangesti Lawang. Thus, if elderly social interaction the better then the rate of depression in the elderly is increasingly reduced. Advice the elderly expected to increase social interaction to prevent the occurrence of depression with social activities or daily activities so that it can social interaction.